Libraries and information utilities [soundrecording] what's the utility of an information utilityn - Parker, Edmond; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp., 1973)
Shows that libraries make their services available through an information channel by cable television.
American Library Association, 91st annual conference. Media: man, material, machine.
Keywords: Libraries and television -- Congresses; Information service -- Congresses; Libraries and media -- Congresses; Communication; Library science; Mass communication